2005
DOI: 10.1021/bi050459b
|View full text |Cite
|
Sign up to set email alerts
|

Acylation of Lysine 860 Allows Tight Binding and Cytotoxicity ofBordetellaAdenylate Cyclase on CD11b-Expressing Cells

Abstract: The Bordetella adenylate cyclase toxin-hemolysin (CyaA, ACT, or AC-Hly) forms cation-selective membrane channels and delivers into the cytosol of target cells an adenylate cyclase domain (AC) that catalyzes uncontrolled conversion of cellular ATP to cAMP. Both toxin activities were previously shown to depend on post-translational activation of proCyaA to CyaA by covalent palmitoylation of the internal Lys983 residue (K983). CyaA, however, harbors a second RTX acylation site at residue Lys860 (K860), and the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 45 publications
8
82
0
Order By: Relevance
“…2), it could be estimated that exposure of cells to 3 g/ml CyaA resulted in a [Ca 2ϩ ] i increase from a basal level of ϳ80 nM to a persistent final level of about 2 M. As further shown in Fig. 1, no elevation of [Ca 2ϩ ] i was observed upon exposure of cells to 3 g/ml of the comparably pure but nonacylated pro-CyaA, which binds CD11/CD18 in a nonproductive manner and exhibits only a residual biological activity (53), and neither did an appropriate lipopolysaccharide control (45 EU/ml) that caused no elevation of [Ca 2ϩ ] i (supplemental Fig. 3).…”
Section: Cyaa Promotes Elevation Of Cytosolic Calcium Level In J774amentioning
confidence: 61%
See 2 more Smart Citations
“…2), it could be estimated that exposure of cells to 3 g/ml CyaA resulted in a [Ca 2ϩ ] i increase from a basal level of ϳ80 nM to a persistent final level of about 2 M. As further shown in Fig. 1, no elevation of [Ca 2ϩ ] i was observed upon exposure of cells to 3 g/ml of the comparably pure but nonacylated pro-CyaA, which binds CD11/CD18 in a nonproductive manner and exhibits only a residual biological activity (53), and neither did an appropriate lipopolysaccharide control (45 EU/ml) that caused no elevation of [Ca 2ϩ ] i (supplemental Fig. 3).…”
Section: Cyaa Promotes Elevation Of Cytosolic Calcium Level In J774amentioning
confidence: 61%
“…The reaction was stopped by addition of 100 mM HCl solution containing 0.2% Tween 20, and the samples were boiled for 15 min at 100°C to denature cellular proteins (cAMP is heat-and acid-resistant). The samples were neutralized by addition of 150 mM unbuffered imidazole, and cAMP concentration was determined by an antibody competition immunoassay as described elsewhere (53).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CyaA is produced as an inactive protoxin, which is converted to an active toxin upon posttranslational modification by a dedicated acyltransferase, the product of the CyaC gene (1). This covalent posttranslational fatty acylation, consisting of palmitoylation at the ε-amino groups of Lys 983 and Lys 860 , is required for CD11b/CD18 binding (35) and the insertion of CyaA into target cell membranes and translocation of the catalytic domain into cytosol of cells, as well as for the formation of a cation-selective oligomeric CyaA pore in target cell membranes. We previously showed that CyaA acylation is necessary to strengthen the interaction of the toxin with CD11b cells (35,36), and it remains to be determined whether these fatty acids can interact with TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometric analysis indicated that the toxin produced by the wild-type SH1217 strain of M. haemolytica has only one lysine residue (lysine 554 ) modified by C 14 and C 14 OH fatty acid. This is in contrast to other members of the RTX toxin family, including A. actinomycetemcomitans leukotoxin, E. coli hemolysin (HlyA), and Bordetella pertussis adenylate cyclase toxin-hemolysin (CyaA), where two lysine residues are acylated (32)(33)(34). The fact that peptide 550 -560 resulted from tryptic cleavage of the parental strain, SH1217, but not the mutant SH2099 confirmed that lysine 554 was acylated by C 14 and C 14 OH fatty acid in Lkt from the parent, but not from the mutant strain SH2099.…”
Section: Discussionmentioning
confidence: 85%